Ma [videorecording (DVD)] - Spencer, Octavia; Lewis, Juliette; Silvers, Diana, 1997- (Universal Pictures Home Entertainment, 2019)
Sue Ann, a loner in her quiet Ohio town, is asked by Maggie, a new teenager in town, to buy some booze for her and her friends. Sue Ann sees the chance to make some unsuspecting younger friends. She offers the kids the chance to avoid drinking and driving by hanging out in the basement of her home as long as they abide by the house rules. Her hospitality starts to curdle into obsession, and what began as a teenage dream turns into a terrorizing nightmare.